Prospects for Psychological Support in Interplanetary Expeditions - Gushin, Vadim; Ryumin, Oleg; Karpova, Olga; Rozanov, Ivan; Shved, Dmitry; Yusupova, Anna (Frontiers in Physiology, 2021)
The article gives an overview of Russian experience in psychological support for orbital space flights. It describes procedures that currently exist and may possibly be used in upcoming manned interplanetary flights. The article also considers psychological unfavorable factors of autonomous interplanetary flights, as well as countermeasures, including promising methods of psychological support.